Preparation process of high borosilicate glass and high borosilicate glass tube with diameter of 360MM

By adding nanocomposite additives of modified boron nitride nanosheets and alumina nanoparticles to the boron silicon glass, and combining graphite phase carbon nitride composite powder and ethyl orthosilicate hydrolysate to prepare anticorrosion coatings, the problem of high boron silicon glass being easily deformed and cracked in high temperature environments is solved, and the effect of improving hardness, cold and cold impact resistance and chemical corrosion resistance is achieved.

CN119638187APending Publication Date: 2025-03-18JIANGXI CHUNSHAN NEW ENERGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411992717.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

High borosilicate glass is prone to softening, deformation and cracking in high-temperature environments, and is intolerant to rapid temperature changes, limiting its service life in high-temperature industrial applications.

Method used

By preparing nanocomposite additives, including modified boron nitride nanosheets and alumina nanoparticles, a column-supported structure is formed and added to high borosilicate glass, and anticorrosion coatings are prepared by combining graphite phase carbon nitride composite powder and ethyl orthosilicate hydrolysate to improve the hardness and anti-cold impact performance of the glass.

Benefits of technology

Effectively disperse stress, prevent crack propagation, improve the hardness and cold impact resistance of high borosilicate glass, reduce cracking risks, and significantly improve its chemical corrosion resistance and light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223974610000091
    Figure BDA0005223974610000091
Patent Text Reader

Abstract

The invention provides high borosilicate glass and a preparation process of a high borosilicate glass tube with the diameter of 360MM, and belongs to the field of glass materials. The high borosilicate glass comprises the following raw material components in percentage by mass: 20-30% of cullet, 8-12% of borax, 1-3% of boric acid, 3-5% of aluminum oxide, 3-5% of sodium oxide, 1-3% of magnesium oxide, 6-8% of a nano composite additive, 0.6-0.8% of lithium oxide, 0.05-0.1% of neodymium oxide, 0.04-0.06% of europium oxide and the balance of quartz sand, the high borosilicate glass tube comprises an amorphous phase layer, a microcrystalline layer wrapping the amorphous phase layer and an anticorrosive coating wrapping the microcrystalline layer. The preparation method comprises the following steps: firstly modifying boron nitride nanosheets, then mixing the modified boron nitride nanosheets with alumina sol to prepare a nano-composite additive with alumina particles uniformly distributed among the boron nitride nanosheets to form a pillared structure, adding the nano-composite additive into high borosilicate glass, and carrying out heat treatment to obtain the high borosilicate glass. The hardness and the cold and hot impact resistance of the high borosilicate glass can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of glass materials, and in particular to a preparation process of high borosilicate glass and a high borosilicate glass tube with a diameter of 360 mm. Background Art

[0002] As an important glass material, high borosilicate glass is widely used in many fields due to its unique properties, such as chemical industry, medicine, lighting, kitchenware, aerospace, etc.

[0003] However, when the temperature rises, the thermal motion of atoms or molecules inside the glass intensifies, which can lead to changes in the glass structure, such as softening, deformation, and even crystallization. This will not only affect the physical properties of the glass, but may also reduce its chemical stability, limiting its application in components that need to withstand high temperature environments for a long time, such as high-temperature industrial furnace observation windows and high-temperature lamp shades. In addition, when traditional high-borosilicate glass experiences rapid temperature changes, it will produce large thermal stresses due to the uneven thermal expansion and contraction inside and on the surface of the glass. When the thermal stress exceeds the strength limit of the glass, it will cause cracks to form and expand, ultimately leading to the breakage of the glass.

[0004] Therefore, it is necessary to propose a preparation process of high borosilicate glass with good chemical stability and resistance to thermal shock and a high borosilicate glass tube with a diameter of 360MM to extend its service life. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention aims to provide a preparation process of high borosilicate glass and a high borosilicate glass tube with a diameter of 360MM.

[0006] A high borosilicate glass comprises the following raw material components, measured by mass percentage: 20-30% of broken glass, 8-12% of borax, 1-3% of boric acid, 3-5% of aluminum oxide, 3-5% of sodium oxide, 1-3% of magnesium oxide, 6-8% of nano-composite additives, 0.6-0.8% of lithium oxide, 0.05-0.1% of neodymium oxide, 0.04-0.06% of europium oxide, and the balance is quartz sand; wherein the preparation steps of the nano-composite additive are as follows:

[0007] Adding boron nitride nanosheets into deionized water and ultrasonically dispersing for 20-30 minutes to obtain a boron nitride nanosheet dispersion with a concentration of 1.3-1.5 mg / mL;

[0008] Add 3-aminopropyltriethoxysilane to the boron nitride nanosheet dispersion at a volume ratio of 1: (90-100), stir at a rate of 300-400 r / min for 8-10 hours, centrifuge, wash and dry to obtain modified boron nitride nanosheets;

[0009] Aluminum isopropoxide is added to anhydrous ethanol at a solid-liquid ratio of 1 g: (10-14) mL while stirring to form a transparent solution, and then glacial acetic acid and deionized water are added, and stirring is continued for 2-3 hours. After standing and aging for 20-24 hours, an alumina sol is obtained;

[0010] The modified boron nitride nanosheets are dispersed in deionized water at a solid-liquid ratio of 1 g: (20-30) mL to form a modified boron nitride nanosheet dispersion, which is then mixed with the alumina sol, and hexadecyltrimethylammonium bromide is added, and ultrasonic treatment is performed for 1-2 hours to obtain a suspension;

[0011] The suspension is dried at 60-80°C for 10-12h, placed in a muffle furnace, heated to 500-600°C at 5°C / min in an air atmosphere and kept warm for 1-2h, then transferred to a tubular furnace, sintered at 1400-1600°C for 2-4h under argon protection, and cooled to obtain a nanocomposite additive.

[0012] Furthermore, the volume ratio of glacial acetic acid, deionized water and anhydrous ethanol is 1:(15-25):(75-95).

[0013] Furthermore, the molar ratio of the modified boron nitride nanosheets to aluminum isopropoxide is 1:(3-5), and the mass ratio of hexadecyltrimethylammonium bromide to the modified boron nitride nanosheets is 1:(90-100).

[0014] Furthermore, a method for preparing a high borosilicate glass tube with a diameter of 360 MM using the above-mentioned high borosilicate glass comprises the following steps:

[0015] S1: mixing quartz sand, broken glass, borax, boric acid, aluminum oxide, sodium oxide, magnesium oxide, nanocomposite additives, lithium oxide, neodymium oxide and europium oxide, and then placing them in a high-temperature furnace, heating and melting them to obtain glass liquid;

[0016] S2: When the glass liquid is cooled to 1200-1250°C, it is drawn out by a multi-axis rotary tube drawing process, and kept at 600-700°C for 2-3 hours. After cooling to room temperature with the furnace, it is heated at 700-750°C for crystallization for 5-6 hours to obtain a base tube;

[0017] S3: Immerse the above-mentioned base tube in the anti-corrosion coating solution for 3-5 minutes. After taking it out, put it into a tubular atmosphere furnace. Under nitrogen protection, heat it to 100-120°C at 2°C / min and keep it warm for 1-2 hours. Then heat it to 600-800°C at 5°C / min and keep it warm for 2-3 hours to form an anti-corrosion coating. After cooling to room temperature with the furnace, a high borosilicate glass tube is obtained.

[0018] Furthermore, the preparation steps of the anti-corrosion coating solution are as follows:

[0019] Add the graphite phase carbon nitride composite powder into deionized water at a solid-liquid ratio of 1 g: (200-300) mL, and perform ultrasonic treatment for 2-3 hours to obtain a graphite phase carbon nitride composite powder dispersion;

[0020] Mix ethyl orthosilicate and ethanol in a volume ratio of 1:(1.3-1.5), add hydrochloric acid solution while stirring, heat and stir at 30-40°C for 18-20h to obtain ethyl orthosilicate hydrolyzate;

[0021] The graphite phase carbon nitride composite powder and the graphite phase carbon nitride composite powder dispersion are added to the ethyl orthosilicate hydrolyzate, and the mixture is stirred for 6-8 hours to obtain an anti-corrosion coating solution.

[0022] Furthermore, the preparation steps of the graphite phase carbon nitride composite powder are as follows:

[0023] Thoroughly mix tin tetrachloride pentahydrate and thiourea at a mass ratio of 1:(40-50), then add them into deionized water at a solid-liquid ratio of 1g:(16-20)mL, stir and dissolve them to obtain a mixed aqueous solution;

[0024] The mixed aqueous solution is heated and dried at 60-80°C to constant weight, then placed in a muffle furnace, heated to 500-600°C at 5-10°C / min, and kept heated for 2-3h. After cooling to room temperature with the furnace, it is ground and sieved to obtain a graphite phase carbon nitride composite powder.

[0025] Furthermore, the solid-liquid ratio of the graphite phase carbon nitride composite powder, the graphite phase carbon nitride composite powder dispersion and the tetraethyl orthosilicate hydrolyzate is 1 g: (280-300) mL: (150-200) mL.

[0026] Furthermore, the diameter of the high borosilicate glass tube is 360 mm.

[0027] Furthermore, the high borosilicate glass tube includes an amorphous phase layer, a microcrystalline layer covering the amorphous phase layer, and an anti-corrosion coating covering the microcrystalline layer.

[0028] Compared with the prior art, the present invention has at least the following beneficial effects:

[0029] 1. The present invention first modifies boron nitride nanosheets with 3-aminopropyltriethoxysilane, then disperses the modified boron nitride nanosheets in deionized water, and mixes them with alumina sol. After drying and high-temperature sintering, a nanocomposite additive in which alumina particles are uniformly distributed between boron oxide nanosheets to form a pillar structure is prepared. After adding the nanocomposite additive to high borosilicate glass, on the one hand, due to the strong interface bonding between the boron nitride nanosheets and the alumina nanoparticles in the nanocomposite additive and its good compatibility with the high borosilicate glass matrix, stress can be effectively dispersed to prevent crack propagation, and the presence of alumina nanoparticles and boron nitride nanosheets will hinder the movement of dislocations, thereby effectively improving the hardness of the high borosilicate glass. On the other hand, since both the boron nitride nanosheets and the alumina nanoparticles have a low thermal expansion coefficient, when the nanocomposite additive is embedded in the high borosilicate glass matrix, the overall thermal expansion coefficient can be further reduced, and the stress concentration caused by temperature changes can be reduced, thereby improving its resistance to cold and hot shocks and reducing the risk of cracking of the high borosilicate glass in a cold and hot alternating environment.

[0030] 2. The present invention prepares graphite-phase carbon nitride composite powder by first using tin tetrachloride pentahydrate and thiourea as raw materials, and then prepares the graphite-phase carbon nitride composite powder into an aqueous dispersion, and then mixes the graphite-phase carbon nitride composite powder and tetraethyl orthosilicate hydrolyzate to form an anti-corrosion coating solution, immerses the substrate pipe in the anti-corrosion coating solution, and then forms an anti-corrosion coating through high-temperature heat treatment. Since the graphite-phase carbon nitride composite powder has excellent chemical stability and the silicon dioxide formed by the tetraethyl orthosilicate hydrolyzate also has extremely high chemical inertness, the anti-corrosion coating prepared by mixing the two can construct a dense barrier, effectively preventing external chemicals from directly contacting the substrate pipe, thereby significantly reducing the penetration and erosion of the substrate pipe by the chemicals, thereby achieving the effect of further improving the chemical corrosion resistance of the high borosilicate glass tube.

[0031] 3. The present invention can play a heterogeneous nucleation role in the glass melt by adding neodymium oxide and europium oxide. During the heat treatment of the glass, they can provide additional nucleation sites, thereby increasing the number of nucleated crystals. Due to the increase in nucleation points, the available space and material supply during crystal growth are relatively dispersed, thereby inhibiting the excessive growth of grains and achieving the effect of grain refinement. In addition, neodymium oxide can promote the dissolution and uniform distribution of europium oxide, while europium oxide can enhance the nucleation ability of neodymium oxide. The synergy of the two can make the grain refinement effect more significant, thereby effectively improving the light transmittance of high borosilicate glass. DETAILED DESCRIPTION

[0032] The following is a detailed description of the preparation process of a high borosilicate glass and a high borosilicate glass tube with a diameter of 360MM provided by the present invention in conjunction with specific embodiments.

[0033] Example 1

[0034] A preparation process of a 360MM diameter high borosilicate glass tube comprises the following steps:

[0035] (1) Preparation of nanocomposite additives:

[0036] Boron nitride nanosheets were added to deionized water and ultrasonically dispersed for 20 minutes to obtain a boron nitride nanosheet dispersion with a concentration of 1.3 mg / mL. Then, 3-aminopropyltriethoxysilane was added to the boron nitride nanosheet dispersion at a volume ratio of 1:90, and stirred at a rate of 300 r / min for 8 hours. After centrifugal separation, washing and drying, modified boron nitride nanosheets were obtained. Subsequently, aluminum isopropoxide was added to anhydrous ethanol at a solid-liquid ratio of 1g:10mL while stirring to form a transparent solution. Glacial acetic acid and deionized water were then added and stirred for 2 hours. After standing and aging for 20 hours, an alumina sol was obtained, in which the volume ratio of glacial acetic acid, deionized water and anhydrous ethanol was 1:15:75. Then, Solid-liquid ratio 1g: 20mL The modified boron nitride nanosheets are dispersed in deionized water to form a modified boron nitride nanosheet dispersion, which is then mixed with the alumina sol, and hexadecyltrimethylammonium bromide is added, and ultrasonic treatment is performed for 1h to obtain a suspension, wherein the molar ratio of the modified boron nitride nanosheets to aluminum isopropoxide is 1:3, and the mass ratio of hexadecyltrimethylammonium bromide to the modified boron nitride nanosheets is 1:90. Finally, the suspension is dried at 60°C for 10h, and then placed in a muffle furnace, heated to 500°C at 5°C / min in an air atmosphere and kept warm for 1h, and then transferred to a tubular furnace, sintered at 1400°C for 2h under argon protection, and cooled to obtain a nanocomposite additive;

[0037] (2) Preparation of graphite phase carbon nitride composite powder:

[0038] The tin tetrachloride pentahydrate and thiourea are fully mixed at a mass ratio of 1:40, and then added to deionized water at a solid-liquid ratio of 1g:16mL, and fully stirred to dissolve to obtain a mixed aqueous solution, and then the mixed aqueous solution is heated and dried at 60°C to constant weight, and then placed in a muffle furnace, and the temperature is increased to 500°C at 5°C / min, and the temperature is kept and heated for 2h, and after cooling to room temperature with the furnace, it is ground and sieved to obtain a graphite phase carbon nitride composite powder;

[0039] (3) Preparation of anti-corrosion coating solution:

[0040] The graphite phase carbon nitride composite powder prepared in (2) is added to deionized water at a solid-liquid ratio of 1g:200mL, and ultrasonically treated for 2h to obtain a graphite phase carbon nitride composite powder dispersion. Then, tetraethyl orthosilicate and ethanol are stirred and mixed at a volume ratio of 1:1.3, and hydrochloric acid solution is added while stirring. The mixture is heated and stirred at 30°C for 18h to obtain a tetraethyl orthosilicate hydrolyzate, wherein the volume ratio of hydrochloric acid solution to tetraethyl orthosilicate is 1:2.5, and the concentration of hydrochloric acid solution is 1.3mol / L. Finally, the above-mentioned graphite phase carbon nitride composite powder and the above-mentioned graphite phase carbon nitride composite powder dispersion are added to the above-mentioned tetraethyl orthosilicate hydrolyzate, and the mixture is kept warm and stirred for 6h to obtain an anti-corrosion coating solution, wherein the solid-liquid ratio of the graphite phase carbon nitride composite powder, the graphite phase carbon nitride composite powder dispersion and the tetraethyl orthosilicate hydrolyzate is 1g:280mL:150mL.

[0041] S1: 57.31% quartz sand, 20% broken glass, 8% borax, 1% boric acid, 3% aluminum oxide, 3% sodium oxide, 1% magnesium oxide, 6% nanocomposite additives, 0.6% lithium oxide, 0.05% neodymium oxide and 0.04% europium oxide are mixed and ball-milled, and then placed in a high-temperature furnace, heated and melted to obtain glass liquid;

[0042] S2: When the glass liquid is cooled to 1200°C, it is drawn out by a multi-axis rotary tube drawing process, and kept at 600°C for 2 hours. After cooling to room temperature with the furnace, it is heated at 700°C for crystallization for 5 hours to obtain a base tube;

[0043] S3: Immerse the above-mentioned base tube in the anti-corrosion coating solution for 3 minutes. After taking it out, put it into a tubular atmosphere furnace. Under nitrogen protection, heat it to 100°C at 2°C / min and keep it warm for 1 hour. Then heat it to 600°C at 5°C / min and keep it warm for 2 hours to form an anti-corrosion coating. After cooling to room temperature in the furnace, a high borosilicate glass tube with a diameter of 360 mm is obtained, and the high borosilicate glass tube includes an amorphous phase layer, a microcrystalline layer covering the amorphous phase layer, and an anti-corrosion coating covering the microcrystalline layer.

[0044] Example 2

[0045] A preparation process of a 360MM diameter high borosilicate glass tube comprises the following steps:

[0046] (1) Preparation of nanocomposite additives:

[0047] Boron nitride nanosheets were added to deionized water and ultrasonically dispersed for 25 minutes to obtain a boron nitride nanosheet dispersion with a concentration of 1.4 mg / mL. Then, 3-aminopropyltriethoxysilane was added to the boron nitride nanosheet dispersion at a volume ratio of 1:95, and stirred at a rate of 350 r / min for 9 hours. After centrifugal separation, washing and drying, modified boron nitride nanosheets were obtained. Subsequently, aluminum isopropoxide was added to anhydrous ethanol at a solid-liquid ratio of 1g:12mL while stirring to form a transparent solution. Glacial acetic acid and deionized water were then added and stirred for 2.5 hours. After standing and aging for 22 hours, an alumina sol was obtained, in which the volume ratio of glacial acetic acid, deionized water and anhydrous ethanol was 1:20:85. Then, the solid-liquid ratio was 1g:12mL and the volume ratio of 1:20:85 was 1:20:85. The modified boron nitride nanosheets are dispersed in deionized water at a liquid ratio of 1g:25mL to form a modified boron nitride nanosheet dispersion, which is then mixed with the alumina sol, and hexadecyltrimethylammonium bromide is added, and ultrasonic treatment is performed for 1.5h to obtain a suspension, wherein the molar ratio of the modified boron nitride nanosheets to aluminum isopropoxide is 1:4, and the mass ratio of hexadecyltrimethylammonium bromide to the modified boron nitride nanosheets is 1:95. Finally, the suspension is dried at 70°C for 11h, and then placed in a muffle furnace, and heated to 550°C at 5°C / min in an air atmosphere and kept warm for 1.5h, and then transferred to a tubular furnace, sintered at 1500°C for 3h under argon protection, and cooled to obtain a nanocomposite additive;

[0048] (2) Preparation of graphite phase carbon nitride composite powder:

[0049] The tin tetrachloride pentahydrate and thiourea were fully mixed at a mass ratio of 1:45, and then added into deionized water at a solid-liquid ratio of 1g:18mL, and fully stirred to dissolve to obtain a mixed aqueous solution, and then the mixed aqueous solution was heated and dried at 70°C to constant weight, and then placed in a muffle furnace, and the temperature was increased to 550°C at 7.5°C / min, and kept heated for 2.5h, and after cooling to room temperature with the furnace, ground and sieved to obtain a graphite phase carbon nitride composite powder;

[0050] (3) Preparation of anti-corrosion coating solution:

[0051] The graphite phase carbon nitride composite powder prepared in (2) is added into deionized water at a solid-liquid ratio of 1 g:250 mL, and ultrasonically treated for 2.5 h to obtain a graphite phase carbon nitride composite powder dispersion. Then, tetraethyl orthosilicate and ethanol are stirred and mixed at a volume ratio of 1:1.4, and then hydrochloric acid solution is added while stirring. The mixture is heated and stirred at 35°C for 19 h to obtain a tetraethyl orthosilicate hydrolyzate, wherein the volume ratio of the hydrochloric acid solution to tetraethyl orthosilicate is 1:3, and the concentration of the hydrochloric acid solution is 1.3 mol / L. Finally, the above-mentioned graphite phase carbon nitride composite powder and the above-mentioned graphite phase carbon nitride composite powder dispersion are added into the above-mentioned tetraethyl orthosilicate hydrolyzate, and the mixture is kept warm and stirred for 7 h to obtain an anti-corrosion coating solution, wherein the solid-liquid ratio of the graphite phase carbon nitride composite powder, the graphite phase carbon nitride composite powder dispersion and the tetraethyl orthosilicate hydrolyzate is 1 g:290 mL:175 mL.

[0052] S1: 45.175% quartz sand, 25% broken glass, 10% borax, 2% boric acid, 4% aluminum oxide, 4% sodium oxide, 2% magnesium oxide, 7% nanocomposite additives, 0.7% lithium oxide, 0.075% neodymium oxide and 0.05% europium oxide are mixed and ball-milled, and then placed in a high-temperature furnace, heated and melted to obtain glass liquid;

[0053] S2: When the glass liquid is cooled to 1225°C, it is drawn out by a multi-axis rotary tube drawing process, and kept at 650°C for 2.5 hours. After cooling to room temperature with the furnace, it is heated at 725°C for crystallization for 5.5 hours to obtain a base tube;

[0054] S3: Immerse the above-mentioned base tube in the anti-corrosion coating solution for 4 minutes. After taking it out, put it into a tubular atmosphere furnace. Under nitrogen protection, heat it to 110°C at 2°C / min and keep it warm for 1.5 hours. Then heat it to 700°C at 5°C / min and keep it warm for 2.5 hours to form an anti-corrosion coating. After cooling to room temperature with the furnace, a high borosilicate glass tube with a diameter of 360 mm is obtained, and the high borosilicate glass tube includes an amorphous phase layer, a microcrystalline layer covering the amorphous phase layer, and an anti-corrosion coating covering the microcrystalline layer.

[0055] Example 3

[0056] A preparation process of a 360MM diameter high borosilicate glass tube comprises the following steps:

[0057] (1) Preparation of nanocomposite additives:

[0058] Boron nitride nanosheets were added to deionized water and ultrasonically dispersed for 30 minutes to obtain a boron nitride nanosheet dispersion with a concentration of 1.5 mg / mL. Then, 3-aminopropyltriethoxysilane was added to the boron nitride nanosheet dispersion at a volume ratio of 1:100, and stirred at a rate of 400 r / min for 10 hours. After centrifugal separation, washing and drying, modified boron nitride nanosheets were obtained. Subsequently, aluminum isopropoxide was added to anhydrous ethanol at a solid-liquid ratio of 1g:14mL while stirring to form a transparent solution. Glacial acetic acid and deionized water were then added and stirred for 3 hours. After standing and aging for 24 hours, an alumina sol was obtained, in which the volume ratio of glacial acetic acid, deionized water and anhydrous ethanol was 1:25:95. Then, Solid-liquid ratio 1g:30mL The modified boron nitride nanosheets are dispersed in deionized water to form a modified boron nitride nanosheet dispersion, which is then mixed with the alumina sol, and hexadecyltrimethylammonium bromide is added, and ultrasonic treatment is performed for 2h to obtain a suspension, wherein the molar ratio of the modified boron nitride nanosheets to aluminum isopropoxide is 1:5, and the mass ratio of hexadecyltrimethylammonium bromide to the modified boron nitride nanosheets is 1:100. Finally, the suspension is dried at 80°C for 12h, and then placed in a muffle furnace, heated to 600°C at 5°C / min in an air atmosphere and kept warm for 2h, and then transferred to a tubular furnace, sintered at 1600°C for 4h under argon protection, and cooled to obtain a nanocomposite additive;

[0059] (2) Preparation of graphite phase carbon nitride composite powder:

[0060] The tin tetrachloride pentahydrate and thiourea are fully mixed at a mass ratio of 1:50, and then added to deionized water at a solid-liquid ratio of 1g:20mL, and fully stirred to dissolve to obtain a mixed aqueous solution, and then the mixed aqueous solution is heated and dried at 80°C to constant weight, and then placed in a muffle furnace, and the temperature is increased to 600°C at 10°C / min, and the temperature is kept and heated for 3h, and after cooling to room temperature with the furnace, it is ground and sieved to obtain a graphite phase carbon nitride composite powder;

[0061] (3) Preparation of anti-corrosion coating solution:

[0062] The graphite phase carbon nitride composite powder prepared in (2) is added to deionized water at a solid-liquid ratio of 1g:300mL, and ultrasonically treated for 3h to obtain a graphite phase carbon nitride composite powder dispersion. Then, tetraethyl orthosilicate and ethanol are stirred and mixed at a volume ratio of 1:1.5, and hydrochloric acid solution is added while stirring. The mixture is heated and stirred at 40°C for 20h to obtain a tetraethyl orthosilicate hydrolyzate, wherein the volume ratio of the hydrochloric acid solution to tetraethyl orthosilicate is 1:3.5, and the concentration of the hydrochloric acid solution is 1.3mol / L. Finally, the above-mentioned graphite phase carbon nitride composite powder and the above-mentioned graphite phase carbon nitride composite powder dispersion are added to the above-mentioned tetraethyl orthosilicate hydrolyzate, and the mixture is kept warm and stirred for 8h to obtain an anti-corrosion coating solution, wherein the solid-liquid ratio of the graphite phase carbon nitride composite powder, the graphite phase carbon nitride composite powder dispersion and the tetraethyl orthosilicate hydrolyzate is 1g:300mL:200mL.

[0063] S1: 33.04% quartz sand, 30% broken glass, 12% borax, 3% boric acid, 5% aluminum oxide, 5% sodium oxide, 3% magnesium oxide, 8% nanocomposite additives, 0.8% lithium oxide, 0.1% neodymium oxide and 0.06% europium oxide are mixed and ball-milled, and then placed in a high-temperature furnace, heated and melted to obtain glass liquid;

[0064] S2: When the glass liquid is cooled to 1250°C, it is drawn out by a multi-axis rotary tube drawing process, and kept at 700°C for 3 hours. After cooling to room temperature with the furnace, it is heated at 750°C for crystallization for 6 hours to obtain a base tube;

[0065] S3: Immerse the above-mentioned base tube in the anti-corrosion coating solution for 5 minutes. After taking it out, put it into a tubular atmosphere furnace. Under nitrogen protection, heat it to 120°C at 2°C / min and keep it warm for 2 hours. Then heat it to 800°C at 5°C / min and keep it warm for 3 hours to form an anti-corrosion coating. After cooling to room temperature with the furnace, a high borosilicate glass tube with a diameter of 360 mm is obtained, and the high borosilicate glass tube includes an amorphous phase layer, a microcrystalline layer covering the amorphous phase layer, and an anti-corrosion coating covering the microcrystalline layer.

[0066] Comparative Example 1

[0067] The difference between Comparative Example 1 and Example 1 is that the nanocomposite additive in step S1 is removed.

[0068] Comparative Example 2

[0069] The difference between Comparative Example 2 and Example 1 is that step S3 is removed, that is, the anti-corrosion coating is not prepared on the base pipe.

[0070] Comparative Example 3

[0071] The difference between Comparative Example 3 and Example 1 is that the neodymium oxide in step S1 is replaced by an equal amount of europium oxide.

[0072] Comparative Example 4

[0073] The difference between Comparative Example 4 and Example 1 is that the europium oxide in step S1 is replaced by an equal amount of neodymium oxide.

[0074] Performance testing:

[0075] 1. The hardness of the high borosilicate glass tubes prepared in Examples 1-3 and Comparative Example 1 was tested with reference to GB / T6739-1996 standard. The results are shown in Table 1.

[0076] 2. The high borosilicate glass tubes prepared in Examples 1-3 and Comparative Example 1 were first placed at 300°C for 1 hour, and then immediately placed at 0°C for 1 hour. After alternating for 5 times, it was observed whether cracking occurred. If no cracking occurred, it was judged as "good", and if cracking occurred, it was judged as "poor". The results are shown in Table 1.

[0077] Table 1: Comparison of hardness and high temperature resistance test results of Examples 1-3 and Comparative Example 1

[0078] Hardness(GPa) Thermal shock resistance Example 1 8.49 good Example 2 8.53 good Example 3 8.58 good Comparative Example 1 5.06 Difference

[0079] It can be seen from Table 1 that when no nano-composite additive is added in Comparative Example 1, the hardness of the obtained high borosilicate glass tube is about 5.06 GPa, and cracking occurs after being treated alternately at 300°C and 0°C for 5 times, indicating that by first modifying the boron nitride nanosheets with 3-aminopropyltriethoxysilane, dispersing the modified boron nitride nanosheets in deionized water, and mixing with alumina sol, drying and high-temperature sintering, a nano-composite additive in which alumina particles are uniformly distributed between the boron oxide nanosheets to form a pillar structure is prepared. After adding the nano-composite additive to the high borosilicate glass, the hardness and resistance to cold and hot shock of the high borosilicate glass tube can be effectively improved, thereby reducing the risk of cracking.

[0080] 3. The borosilicate glass tubes prepared in Examples 1-3 and Comparative Example 2 were placed in 1 mol / L HCl solution and 5% sodium hydroxide solution, respectively. After soaking for 15 days, the Li content in the soaking solution was analyzed using ICP-OES. + 、Al 3+ concentration.

[0081] Table 2: Comparison of chemical corrosion resistance results of Examples 1-3 and Comparative Example 2

[0082]

[0083] As can be seen from Table 2, in Comparative Example 2, after the anti-corrosion coating is not prepared on the surface of the base tube, the obtained high borosilicate glass tube is immersed in acid solution and alkaline solution for 15 days, and the leached aluminum ions and sodium ions are much higher than those in Examples 1-3. It can be seen that by first preparing a graphite phase carbon nitride composite powder with tin tetrachloride pentahydrate and thiourea as raw materials, preparing it into an aqueous dispersion, and then mixing it with the graphite phase carbon nitride composite powder and ethyl orthosilicate hydrolyzate to prepare an anti-corrosion coating solution, immersing the base tube in the anti-corrosion coating solution, and then forming an anti-corrosion coating through high-temperature heat treatment, the penetration and erosion of the base tube by chemical substances can be significantly reduced, thereby further improving the chemical corrosion resistance of the high borosilicate glass tube.

[0084] 4. Referring to GBT26810-2011 standard, the light transmittance of the high borosilicate glass prepared in Examples 1-3 and Comparative Examples 3-4 was measured using a UV-3600 spectrophotometer. The results are shown in Table 3.

[0085] Table 3: Comparison of hardness and high temperature resistance test results of Examples 1-3 and Comparative Example 1

[0086] Light transmittance (%) Example 1 96 Example 2 96 Example 3 96 Comparative Example 3 75 Comparative Example 4 83

[0087] It can be seen from Table 3 that when only europium oxide or only neodymium oxide is added in Comparative Examples 3 and 4, the transmittance of the obtained high borosilicate glass is 75% and 83% respectively, which is much lower than the transmittance of the high borosilicate glass obtained by adding europium oxide and neodymium oxide at the same time in Examples 1-3. It can be seen that the synergy of europium oxide and neodymium oxide can make the grain refinement effect more significant, thereby effectively improving the transmittance of the high borosilicate glass.

[0088] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A high borosilicate glass, characterized in that: The raw material components include, by mass percentage, 20-30% of broken glass, 8-12% of borax, 1-3% of boric acid, 3-5% of aluminum oxide, 3-5% of sodium oxide, 1-3% of magnesium oxide, 6-8% of nano-composite additives, 0.6-0.8% of lithium oxide, 0.05-0.1% of neodymium oxide, 0.04-0.06% of europium oxide, and the balance is quartz sand; wherein the preparation steps of the nano-composite additive are as follows: Adding boron nitride nanosheets into deionized water and ultrasonically dispersing for 20-30 minutes to obtain a boron nitride nanosheet dispersion with a concentration of 1.3-1.5 mg / mL; Add 3-aminopropyltriethoxysilane to the boron nitride nanosheet dispersion at a volume ratio of 1: (90-100), stir at a rate of 300-400 r / min for 8-10 hours, centrifuge, wash and dry to obtain modified boron nitride nanosheets; Aluminum isopropoxide is added to anhydrous ethanol at a solid-liquid ratio of 1 g: (10-14) mL while stirring to form a transparent solution, and then glacial acetic acid and deionized water are added, and stirring is continued for 2-3 hours. After standing and aging for 20-24 hours, an alumina sol is obtained; The modified boron nitride nanosheets are dispersed in deionized water at a solid-liquid ratio of 1 g: (20-30) mL to form a modified boron nitride nanosheet dispersion, which is then mixed with the alumina sol, and hexadecyltrimethylammonium bromide is added, and ultrasonic treatment is performed for 1-2 hours to obtain a suspension; The suspension is dried at 60-80°C for 10-12h, placed in a muffle furnace, heated to 500-600°C at 5°C / min in an air atmosphere and kept warm for 1-2h, then transferred to a tubular furnace, sintered at 1400-1600°C for 2-4h under argon protection, and cooled to obtain a nanocomposite additive.

2. The high borosilicate glass according to claim 1, characterized in that: The volume ratio of glacial acetic acid, deionized water and anhydrous ethanol is 1:(15-25):(75-95).

3. The high borosilicate glass according to claim 1, characterized in that: The molar ratio of the modified boron nitride nanosheets to aluminum isopropoxide is 1:(3-5), and the mass ratio of hexadecyltrimethylammonium bromide to the modified boron nitride nanosheets is 1:(90-100).

4. A method for preparing a high borosilicate glass tube with a diameter of 360 MM using the high borosilicate glass according to claims 1-3, characterized in that: The steps include: S1: mixing quartz sand, broken glass, borax, boric acid, aluminum oxide, sodium oxide, magnesium oxide, nanocomposite additives, lithium oxide, neodymium oxide and europium oxide, and then placing them in a high-temperature furnace, heating and melting them to obtain glass liquid; S2: When the glass liquid is cooled to 1200-1250°C, it is drawn out by a multi-axis rotary tube drawing process, and kept at 600-700°C for 2-3 hours. After cooling to room temperature with the furnace, it is heated at 700-750°C for crystallization for 5-6 hours to obtain a base tube; S3: Immerse the above-mentioned base tube in the anti-corrosion coating solution for 3-5 minutes. After taking it out, put it into a tubular atmosphere furnace. Under nitrogen protection, heat it to 100-120°C at 2°C / min and keep it warm for 1-2 hours. Then heat it to 600-800°C at 5°C / min and keep it warm for 2-3 hours to form an anti-corrosion coating. After cooling to room temperature with the furnace, a high borosilicate glass tube is obtained.

5. The preparation process of a 360MM diameter high borosilicate glass tube according to claim 4, characterized in that: The steps for preparing the anti-corrosion coating solution are as follows: Add the graphite phase carbon nitride composite powder into deionized water at a solid-liquid ratio of 1 g: (200-300) mL, and perform ultrasonic treatment for 2-3 hours to obtain a graphite phase carbon nitride composite powder dispersion; Mix ethyl orthosilicate and ethanol in a volume ratio of 1:(1.3-1.5), add hydrochloric acid solution while stirring, heat and stir at 30-40°C for 18-20h to obtain ethyl orthosilicate hydrolyzate; The graphite phase carbon nitride composite powder and the graphite phase carbon nitride composite powder dispersion are added to the ethyl orthosilicate hydrolyzate, and the mixture is stirred for 6-8 hours to obtain an anti-corrosion coating solution.

6. The process for preparing a 360MM diameter high borosilicate glass tube according to claim 5, characterized in that: The preparation steps of graphite phase carbon nitride composite powder are as follows: Thoroughly mix tin tetrachloride pentahydrate and thiourea at a mass ratio of 1:(40-50), then add them into deionized water at a solid-liquid ratio of 1g:(16-20)mL, stir and dissolve them to obtain a mixed aqueous solution; The mixed aqueous solution is heated and dried at 60-80°C to constant weight, then placed in a muffle furnace, heated to 500-600°C at 5-10°C / min, and kept heated for 2-3h. After cooling to room temperature with the furnace, it is ground and sieved to obtain a graphite phase carbon nitride composite powder.

7. The process for preparing a 360MM diameter high borosilicate glass tube according to claim 5, characterized in that: The volume ratio of the hydrochloric acid solution to tetraethyl orthosilicate is 1:(2.5-3.5), and the concentration of the hydrochloric acid solution is 1.3 mol / L.

8. The process for preparing a 360MM diameter high borosilicate glass tube according to claim 5, characterized in that: The solid-liquid ratio of the graphite phase carbon nitride composite powder, the graphite phase carbon nitride composite powder dispersion and the tetraethyl orthosilicate hydrolyzate is 1g:(280-300)mL:(150-200)mL.

9. The process for preparing a 360MM diameter high borosilicate glass tube according to claim 4, characterized in that: The diameter of the high borosilicate glass tube is 360 mm.

10. The process for preparing a 360MM diameter high borosilicate glass tube according to claim 4, characterized in that: The high borosilicate glass tube comprises an amorphous phase layer, a microcrystalline layer covering the amorphous phase layer, and an anti-corrosion coating covering the microcrystalline layer.

Citation Information

Patent Citations

  • Synthesis and application of graphite phase carbon nitride-ammonium tungsten bronze composite photocatalyst

    CN110801856A

  • Preparation method of high borosilicate glass, high borosilicate glass and application thereof

    CN111592226A

  • Photocatalytic self-cleaning coating as well as preparation method and application thereof

    CN114196241A

  • Glass slurry and preparation method thereof

    CN117303746A

  • Formula for preparing black microcrystalline plate by using iron tailings and preparation method of black microcrystalline plate

    CN117510076A